An Austrian critique of the Prebisch-singer theory of the deterioration in the terms of trade. Issue 4 (31st January 2020) - Futerman, Alan G.; Block, Walter E.
Abstract : Purpose: This study aims to offer a critique of the theory of the deterioration in terms of trade, developed by Raúl Prebisch and Hans Singer. Design/methodology/approach: As an example of the theory's shortcomings, the case of Argentina's import substitution model is analyzed. Findings: This study demonstrates how a misunderstanding of the influence of price variability in international trade may lead to the mistaken conclusion that protectionist measures must be enforced to achieve growth and prosperity. Originality/value: This is the first study that criticizes the Prebisch-Singer theory of the deterioration in the terms of trade from an Austrian economics.